2019
DOI: 10.1038/s41598-019-55516-w
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Deformation in Microgel Filtration

Abstract: Colloidal filtration processes using porous membranes suffer from productivity loss due to colloidal matter retention and continuous build-up by the retained matter. Especially during filtration of soft matter, the deformation of the individual colloids that make up the filter cake may be significant; however, this deformation and its impact remain unresolved so far. Yet, understanding the deformation on the single colloid level as well as on the ensemble level is important to be able to deconvolute filter cak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…These highly ordered areas are labeled in grey indicating half-ordered and half-amorphous regions. This existence of highly ordered areas confirms microfluidic observations of partly crystalline and partly amorphous cakes for jammed colloids 41,42 . Based on experimental phase diagrams generated with pNIPAM microgels, this transition between amorphous and crystalline structures develops in the transition region from fluid to crystal behavior at effective volume factions φ eff ∼ 0.56 43 .…”
Section: Resultssupporting
confidence: 88%
“…These highly ordered areas are labeled in grey indicating half-ordered and half-amorphous regions. This existence of highly ordered areas confirms microfluidic observations of partly crystalline and partly amorphous cakes for jammed colloids 41,42 . Based on experimental phase diagrams generated with pNIPAM microgels, this transition between amorphous and crystalline structures develops in the transition region from fluid to crystal behavior at effective volume factions φ eff ∼ 0.56 43 .…”
Section: Resultssupporting
confidence: 88%
“…This behavior conforms with the expected pressure distribution in the channel, were the strongest pressure gradients are in the most narrow sections. While in previous work 9 , we were able to identify the shape of deformation of individual particles in the filter cake, we can now visualize the gradient formation of filter cakes under filtration conditions on the scale of the particles. To the best of our knowledge, while such behavior could be expected, it was not visualized on the particle scale before the present work.…”
Section: Visualization Of Deformation Gradient By Compression and Relmentioning
confidence: 94%
“…crystalline and amorphous regions in the filter cake [7][8][9] . We found that the crystalline regions in the filter cake facilitate the permeation of the colloids 14 .…”
mentioning
confidence: 99%
“…The colloids are in a fixed position inside the collection and start deforming and narrowing the neighboring colloids' voids. Many different physical phenomena ranging from thermal agitation to compression and deformation, 9,11 as well as interpenetration and crystallization 12,13 are significant. One phenomenon of this glass transition stage is that the packing's morphology and coordination depend on the previous filtration time and applied force.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, minor void size changes induced by particle deformation and cake compression affect the permeation characteristic tremendously. 11,19,20 The most compressed gel layer with the smallest voids next to the membrane dominates the overall pressure loss. 5 This dense gel layer might become a stage three network without voids when filtering tiny and soft colloids at high compression or when particles break by compression.…”
Section: Introductionmentioning
confidence: 99%